Contágio e "Descontágio" entre os mercados financeiros da Argentina e Brasil - Seabra, Fernando; Cazarotto, Simone (Revista Produção Online, 2003)
The objective of this paper is to assess the relationship between the performance of the Ibovespa and the Merval indexes and to test the contagion hypothesis between these two stock markets. The method is graphic and correlation analysis based on weekly data in the period post – apr/01. We have found - as a preliminary result – a significant negative relationship between country risk indicators and stock profitability in both markets. As for the comparative analysis between Merval and Ibovespa indexes, a significant contagion of the Brazilian stock market was found in the first period of the sample (apr/01 – oct/01). However, the contagion hypothesis could no longer be accepted for the second half of the sample (nov/01 – apr/02). The main reason for the disconnection between the two stock markets was the stability of the country risk variable in Brazil as opposed to a remarkable increase in Argentina. The persistence regarding macroeconomic fundamentals and favorable conditions in terms of firm’s competitiveness and profitability can be pointed out as key factors for the recent differentiation of the Brazilian capital market.